Parametric investigation and survey of spintronic sensors v-s electronic sensors (case study: current sensors) - Teklu , Ephrem; Alemu, Getachew (Zede Journal of Ethiopian Engineers and Architects, 2023)
Conventional electronic devices depend on the transport of electrical charge carriers–electrons in a semiconductor such as silicon [1]. Now, however, physicists are trying to exploit the ’spin’ of the electron rather than its charge to create a remarkable new generation of spintronic devices which are smaller, more versatile and more robust than those currently making up silicon chips and circuit elements. Compared with other solid-state sensors, spintronic sensors offer more sensitivity and precision and are not damaged by large magnetic fields. This paper presents the investigation results of the comparison of the conventional electronics current sensors and spintronics current sensors relying on the sensitivity of the two. To extract our conclusion survey of the researches on spintronics sensors and conventional electronic sensors are done separately.